Empire as a form of socio-political existence of Russia - Kirvel, Cheslav S.; Kirvel, Olga Ch. (Journal of the Belarusian State University. Sociology, 2023)
The article is devoted to the investigation of the Russian imperial project and develops the concept of regional new empires. The restore of the empire in a new version may be the optimal solution to the search for an effective government structure in modern Russia. The characteristic features and peculiarities of the traditional Russian Empire are disclosed. The fundamental differences from Western empires of the colonial type include: a humane attitude towards the peoples and ethnic groups included in the Russian Empire, the phenomenon of over-exploitation of the Russian empire-forming people. It is proved that Russia, despite its territorial scope, was not a colonial empire and, unlike Western European countries, the Russians generally had no tradition of exterminating any peoples. The high degree of centralisation of the traditional Russian Empire is explained by the objective conditions of its historical existence. The success of the Russian imperial project in the long term is demonstrated, its achievements in the Soviet era, its ability to revive after unimaginably severe cataclysms, defeats and unrest are shown. It has been established that, following the logic of the historical development of Russia, it is necessary to restore the empire in full as the only form of statehood in which the country can save itself and survive. The restore of the new Russian Empire is possible in the form of a core state-civilisation as a center of gravity for allied states related in cultural and civilisational terms.